2014
DOI: 10.1007/978-1-4939-0817-2_1
|View full text |Cite
|
Sign up to set email alerts
|

Sperm Proteases and Extracellular Ubiquitin–Proteasome System Involved in Fertilization of Ascidians and Sea Urchins

Abstract: Ascidians (primitive chordates) are hermaphroditic animals that release spermatozoa and eggs almost simultaneously, but some species, including Halocynthia roretzi, show strict self-sterility. In H. roretzi, a 70-kDa vitelline coat (VC) protein consisting of 12 EGF-like repeats, named HrVC70, appears to be a promising candidate for the self/nonself-recognition (or allorecognition) system during gamete interaction. After spermatozoon recognizes the VC as nonself, sperm 700-kDa extracellular ubiquitin-conjugatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…In another ascidian H. roretzi , P. depressus (sea urchin), pig (mammal) (reviewed in ), and quail (bird) , the extracellular ubiquitin‐proteasome system on sperm is recognized to function as the egg coat lysin. In H. roretzi , ubiquitination activity in sperm exudate toward a major VC component HrVC70 and proteasome activity on sperm surface were suggested.…”
Section: Discussionmentioning
confidence: 99%
“…In another ascidian H. roretzi , P. depressus (sea urchin), pig (mammal) (reviewed in ), and quail (bird) , the extracellular ubiquitin‐proteasome system on sperm is recognized to function as the egg coat lysin. In H. roretzi , ubiquitination activity in sperm exudate toward a major VC component HrVC70 and proteasome activity on sperm surface were suggested.…”
Section: Discussionmentioning
confidence: 99%
“…Sperm hyaluronidases are believed to play an intriguing role in fertilization in mammals, and sperm-specific SPAM1 and HYAL5 hyaluronidase have been suggested to be involved in sperm-ZP binding in mice. Recent studies have shown that hyaluronidases are not required for fertilization ( 61 , 62 ).…”
Section: The Three Stages Of Fertilizationmentioning
confidence: 99%
“…Although this is considered to be the prevailing molecular mechanism, it is likely that molecules other than glycosidases participate in the initial sperm–oocyte adhesion. Trypsin-like acrosin and spermosin proteases have been proposed to be involved in this process, suggesting that a proteasome system enables spermatozoa to penetrate the chorion or participate in the process as sperm-related ‘moveable’ binding proteins ( Sawada et al ., 2014 ). A conserved mechanism of gamete recognition in mammals is based on carbohydrate–protein interaction between sperm and oocyte.…”
Section: Sperm Activationmentioning
confidence: 99%